Environmental Health Risk Analysis of NH3 Exposure Around a Laying Chicken Farm in Darsono, Jember - Febriyanti Ayuningtyas; Khoiron Khoiron; Rahayu Sri Pujiati; Prehatin Trirahayu Ningrum (Knowledge Dynamics, 2026)
Introduction: Laying hen farming constitutes a vital agricultural subsector that plays a significant role in meeting the demand for animal-based food products. However, livestock production is also recognized as a major source of atmospheric ammonia emissions. Ammonia has a negative impact on public health and the environment. This study aims to analyze the environmental health risks of exposure to ammonia gas around laying hens farms. Methods: The research was carried out using a descriptive design method of environmental health risk analysis (EHRA). The population in this study was the community around the laying hen farm with a sample of 95 respondents. Measurement of ammonia gas was carried out using a spectrophotometer using the Indophenol method based on SNI 19-7119.6-2005. Air samples were taken at three points. Results: The results of this study showed that the largest concentration was 0.00807 mg/Nm3 and the lowest was 0.00711 mg/Nm3. Based on an analysis of environmental health risks, the RQ value at the highest concentration was 0.00466 for the adult population and 0.00618 for the child population. Conclusion: The conclusion of this study is that exposure to ammonia gas in the adult population weighing 55kg and the child population weighing 25kg around the laying hen farm in Darsono Village is still within safe limits for a frequency of 350 days/year for the next 9 years. The advice that can be given is that the farm concerned needs to carry out livestock waste management as a source of ammonia emissions in laying hen farms.